Design of Dual Band Rectifiers for Energy Harvesting Applications - Abdullah Eroglu; Kowshik Dey; Rezwan Hussain; Tunir Dey (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Design, simulation and implementation of dual band radio frequency energy harvesting (RFEH) system operating at 900MHz and 1.8GHz is introduced. In the proposed design, RF-DC conversion system is designed to passively amplify the available voltage for rectification by developing a resonator with high quality factor. Passive amplification and rectification are implemented using a combination of clamper and peak detector circuits. Harmonics presented in the rectified output voltage is eliminated by using an innovative two-section dual band transmission line matching network and filter. Energy harvesting system is designed, simulated and measured. Close agreement has been observed between analytical, simulation and measurement results.